2015
DOI: 10.1371/journal.pone.0136553
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Alterations in Right Dorsomedial Prefrontal and Left Insular Cortex Co-Localize in Adolescents with Aggressive Behaviour: An ALE Meta-Analysis

Abstract: Recent neuroimaging work has suggested that aggressive behaviour (AB) is associated with structural and functional brain abnormalities in processes subserving emotion processing and regulation. However, most neuroimaging studies on AB to date only contain relatively small sample sizes. To objectively investigate the consistency of previous structural and functional research in adolescent AB, we performed a systematic literature review and two coordinate-based activation likelihood estimation meta-analyses on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 166 publications
(278 reference statements)
5
56
0
Order By: Relevance
“…Third, among such young children refusals, drop-outs, and exclusions for motion-flawed data were not uncommon, potentially biasing results, although validity is suggested by certain strong consistencies ( e.g., before risky behaviors all (of many) significant activation:externalizing associations were negative). And again, the similar neural dysfunction of these children and troubled adolescents (Alegria et al, 2016; Raschle et al, 2015; Rogers and De Brito, 2016), although unfortunate, is reassuring.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Third, among such young children refusals, drop-outs, and exclusions for motion-flawed data were not uncommon, potentially biasing results, although validity is suggested by certain strong consistencies ( e.g., before risky behaviors all (of many) significant activation:externalizing associations were negative). And again, the similar neural dysfunction of these children and troubled adolescents (Alegria et al, 2016; Raschle et al, 2015; Rogers and De Brito, 2016), although unfortunate, is reassuring.…”
Section: Discussionmentioning
confidence: 84%
“…Second, our discussion compares children reported here and adolescents reported elsewhere (Alegria et al, 2016; Raschle et al, 2015; Rogers and De Brito, 2016). Such cross-sectional comparisons should inform, but cannot replace, future longitudinal studies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In line with individual reports, meta-analyses have summarized that brain regions commonly affected in conduct disorder are part of specific neural networks, specifically the emotion processing and regulation network (see figure 1) 18,19 . Brain areas within those networks are functionally and structurally interconnected with one another by anatomical white matter tracts consisting of abundant thin myelinated axons.…”
Section: Brain Connectivity In Conduct Disordermentioning
confidence: 77%
“…From a structural perspective, a study of 9-to 18-year-old males and females found that callous-unemotional traits are related to variations in brain structure (i.e., gray matter volume of the bilateral anterior insular cortices), but only in males (Raschle et al, 2018). Other research suggests that aggressive behavior might originate from an impairment of both recognition of stimuli that depict emotional valence and cognitive control of emotional behavior (Sterzer, Stadler, Krebs, Kleinschmidt, & Poustka, 2005), and that adolescents with aggressive behavior may also have significant differences in emotion processing and regulation networks (including orbitofrontal, dorsomedial prefrontal, and limbic cortex) (Raschle, Menks, Fehlbaum, Tshomba, & Stadler, 2015).…”
Section: Fmri Aggression and Cyberbullyingmentioning
confidence: 99%